Antimicrobial activity assessment of time-dependent release bilayer tablets of amoxicillin trihydrate - Sarwar Beg; Amit Kumar Nayak; Kanchan Kohli; Suryakanta Swain; MS Hasnain (Universidade de São Paulo, 2012)
The aim of present study was the assessment of antimicrobial activity of prepared time-dependent release bilayer tablets of amoxicillin trihydrate and in vitro evaluation of drug release by antimicrobial assay using agar plate diffusion method. The bilayer tablets comprised of a delayed and sustained release layer. Direct compression method was used for the preparation of bilayer tablets containing Eudragit-L100 D55 as delayed release polymer, and HPMCK4M and HPMCK15 as sustained release polymers. The prepared bilayer tablets containing amoxicillin trihydrate were evaluated for hardness, thickness, friability, weight variation and drug content. Further, in vitro drug release was assessed by antimicrobial assay using S. aureus and E. coli as test microorganisms. The aliquot samples of in vitro drug release study were found to be effective against both microorganisms for 16 hours due to sustained action. The in vitro drug release study and antimicrobial assay showed that bilayer tablets have sustained release profile of drug delivery with time-dependent burst release after a lag-time of 2 hours. The lower MIC value (2 µg/mL) of prepared bilayer tablets vis-à-vis marketed preparation (5 µg/mL) represented its good antimicrobial activity. O objetivo do presente estudo foi avaliar a atividade antimicrobiana de formulações de comprimidos de dupla camada contendo amoxicilina triidratada para liberação tempo dependente e avaliação da liberação in vitro do fármaco pelo ensaio de atividade antimicrobiana utilizando o método de difusão em placa de ágar. Os comprimidos de dupla camada consistem em uma camada para liberação retardada e outra sustentada. O método de compressão direta foi usado para a preparação dos comprimidos de dupla camada contendo Eudragit-L 100 D55 como polímero para liberação retardada e HPMCK4M ou HPMCK15 como polímeros para liberação sustentada. As formulações de comprimidos de dupla camada contendo amoxicilina triidratada foram avaliadas quanto a dureza, espessura, friabilidade, variação de peso e conteúdo de fármaco. Além disso, a liberação do fármaco in vitro foi avaliada por ensaio de atividade antimicrobiana usando S. aureus e E. coli como microrganismos teste. A alíquota das amostras do estudo de liberação do fármaco in vitro demonstrou ser efetiva contra ambos os microrganismos por um período de 16 horas devido à ação sustentada. O estudo de liberação do fármaco in vitro e o ensaio de atividade antimicrobiana mostraram que os comprimidos de dupla camada tiveram um perfil de liberação sustentada do fármaco com um pico de liberação após 2 horas de ensaio. O menor valor de MIC (2 ug/mL) dos comprimidos de dupla camada quando comparados à formulação comercial (5 ug/mL) representa uma boa atividade antimicrobiana.